Conformational dependence of DNA ballistic conductivity - Starikov, E. B.; Quintilla, A.; Lee, K. H.; Wenzel, W. (AMER INST PHYSICS, 2008)
With the atomistic Kubo-Verges method we calculate the ballistic conductance of various conformers of DNA (A,B,Z), as well as intermediate and composite conformations, using experimental structures and model complexes. For duplexes with 6 and 15 base pairs, we find that the valence band conductivity near the Fermi edge varies dramatically between the different conformations, most notably for the B-to-Z transition. The latter conductivity differences are largely unchanged both in the presence and in the absence of trimethylthiol linkers between DNA and gold electrodes in vacuo, but become much less drastic when explicit molecular dynamics and water-counterion surrounding of B- and Z-DNA are taken into account. Based on atomistic structural models, we argue that changes in the electrostatic energy in the presence of an applied external electric field can induce conformational switching that may be exploited in novel DNA-based memory devices of high packing density. (C) 2008 American Institute of Physics.
Keywords: DOUBLE-STRANDED DNA; B-DNA; CONDUCTANCE; SINGLE